Effect of Media Composition and Oxygen Tension on Cellular Stress Response and Nrf2 Activation in HepG2ARE Cells - Rutt Taba; Marie Põlluaed; Karin Tein; Marju Puurand; Tuuli Käämbre; Anton Terasmaa (Antioxidants)
Cell models play a central role in preclinical research aimed at the mechanism of disease and drug discovery. The outside environment of the cells, including levels of nutrients and oxygen tension, regulates cellular stress response pathways. Routinely used in vitro disease models often overlook cell growth conditions. This study aimed to evaluate the effect of substituting classic cell media (DMEM) with media matching the nutrient composition of human plasma (Plasmax) on cell viability, the activation of nuclear factor erythroid 2-related factor 2 (Nrf2), glutathione (GSH), and malondialdehyde (MDA) levels by different pharmacological inducers of cell stress. The cells were grown at ambient (~19%) and reduced (5%) oxygen levels. The activation of Nrf2 by ferroptosis activators (erastin and RSL3) was dependent on cell media and oxygen tension. The induction of Nrf2 by an inducer of endoplasmic reticulum stress, thapsigargin, was observable only in cells grown in DMEM and at low oxygen tension. GSH and MDA levels were elevated in Plasmax media. Results indicate that stress tolerance and the activation of Nrf2 in the HepG2ARE cell line depend on the growth conditions, including cell media and oxygen. Cell culture conditions should be critically considered when designing in vitro models of diseases involving oxidative stress.